Perianal Endometriosis Mimicking Recurrent Perianal Abscess - Iqbal, Mohd (S. Karger AG, 2009)
Endometriosis of the perianal region is an extremely rare condition usually seen in episiotomy scars and can involve the septum separating vagina and anal canal. The clinician is unlikely to suspect it if there is no scar in the perineum and patient the does not give a history of episiotomy. Moreover it is difficult to suspect when the patient does not report cyclical pain and therefore it is likely to be treated as perianal sepsis. We report the rare case of a 35-year-old woman who presented with recurrent painful nodule of endometriosis of the perianal area without previous episiotomy.